Leverage, Net Working Capital, and Firm Size on Financial Performance of Infrastructure Companies Listed on the Indonesia Stock Exchange - Yohana Putri Evelina Silalahi; Septony Siahaan; Saur Melianna Sipayung; Dimita H P Purba (Manajemen: Jurnal Ekonomi, 2026)
This study examines the effect of leverage, net working capital (NWC), and firm size on the financial performance of infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Financial performance is proxied by Return on Assets (ROA). A quantitative method with multiple linear regression analysis via SPSS 26 was employed, using a purposive sampling technique that yielded 16 companies (75 observations after outlier removal). Results show that leverage has a negative and significant partial effect on ROA; NWC has a negative and significant partial effect on ROA; firm size has a negative and insignificant partial effect on ROA; and all three variables simultaneously exert a significant effect on ROA. The Adjusted R² equals 0.210, indicating these variables collectively explain 21.0% of the variation in financial performance